1996
DOI: 10.3109/00207459608987262
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Weak Electromagnetic Fields on the Amplitude of the Pattern Reversal Vep Response in Parkinson's Disease

Abstract: Visual evoked potential (VEP) studies are widely used for the diagnosis of multiple sclerosis (MS) and are also useful in monitoring the effects of various therapeutic modalities in the disease. Prolongation of the VEP latencies has been demonstrated in patients with MS and in other neurodegenerative disorders including Parkinson's disease (PD), a disorder characterized by deficient cerebral dopamine (DA) functions. Pharmacological and biochemical studies have demonstrated a positive correlation between the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…The EM ®eld stimulatory effect has been observed with the use of low frequencies. Some authors have reported a signi®cant increase in the amplitude of visual evoked potentials on short term exposure in patients with multiple sclerosis with a history of optic neuritis [Sandyk, 1996b] and in patients with Parkinson's disease [Sandyk, 1996a]. In connection with a low frequency EM ®eld, healthy persons were seen to have experienced a positive effect in the form of N1 amplitude enhancement in a dichotic listening task and a negative effect in the form of prolonged reaction time and visual ERP P2 latency [Crasson et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…The EM ®eld stimulatory effect has been observed with the use of low frequencies. Some authors have reported a signi®cant increase in the amplitude of visual evoked potentials on short term exposure in patients with multiple sclerosis with a history of optic neuritis [Sandyk, 1996b] and in patients with Parkinson's disease [Sandyk, 1996a]. In connection with a low frequency EM ®eld, healthy persons were seen to have experienced a positive effect in the form of N1 amplitude enhancement in a dichotic listening task and a negative effect in the form of prolonged reaction time and visual ERP P2 latency [Crasson et al, 1999].…”
Section: Discussionmentioning
confidence: 99%